Implementasi Tasawuf Dalam Pendidikan Agama Islam di Sekolah - Ahmadi, Ahmadi; Moh. Nurhakim; Khozin (STID Raudlatul Iman Sumenep, 2024)
The impression of the loss of manners and ethics in education today is a phenomenon in itself, including in education in Indonesia. Unpraised behaviour in the world of education above would undoubtedly not have happened if all parties prioritised manners, morals and adab. Noble character is one of the things that students must have in addition to the strength of religious spirituality. Religious spirituality has become a new label, style, and identity in educational studies. In Islamic civilisation, spirituality is more synonymous with the term Sufism. This article discusses Sufism as an approach to Islamic religious education which is focused on conventional and transformative Sufism and its implementation in Islamic education in schools. This article uses a literature approach without field research as well as the use of library sources in the form of books, journal articles and other documents that are considered relevant to the discussion. The analysis uses content analysis. From the results of the study, it was found that the implementation of Sufism in Islamic education can be implemented by approaching the relationship between religion and science which offers models of conflict, independence, dialogue and integration. Each of these models has its own consequences. Therefore, in implementing it, it is necessary to consider less harm. Although the implementation is definitely not as easy as imagined. Especially in modern times with the openness of information that can hinder the process of implementing Sufism in Islamic education. Kesan hilangnya adab dan etika dalam pendidikan saat ini menjadi fenonema tersendiri, termasuk juga dalam pendidikan di Indonesia. Prilaku kurang terpuji di dunia pendidikan di atas niscaya tidak akan terjadi jika semua pihak mengedepankan budi pekerti, akhlak dan adab. Akhlak mulia merupakan salah satu hal yang harus dimiliki peserta didik selain kekuatan spritualitas keagamaan. Spiritualitas keagamaan selama ini sudah menjadi label, corak, dan identitas baru dalam kajian pendidikan. Dalam peradaban Islam, spiritualitas lebih identik dengan istilah tasawuf atau sufisme. Artikel ini membahas tentang tasawuf sebagai pendekatan pendidikan agama Islam yang difokuskan pada tasawuf konvensional dan transformatif serta implementasinya dalam pendidikan Islam di sekolah. Artikel ini menggunakan pendekatan kepustakaan tanpa riset lapangan sekaligus pemanfaatan sumber pustaka berupa buku, artikel jurnal dan dokumen lain yang dianggap relevan dengan pembahasan. Adapun analisanya menggunakan content analysis. Dari hasil penelitian ditemukan bahwa implementasi tasawuf dalam pendidikan Islam bisa diimplementasikan dengan pendekataan relasi agama dan sains yang menawarkan model konflik, independensi, dialog dan integrasi. Pada setiap model tersebut memiliki konsekuensi masing-masing. Oleh karenanya dalam mengimplementasikannya perlu mempertimbangkan lebih sedikit mudharatnya. Walaupun dalam implementasinya pasti tidak semudah yang dibayangkan. Terutama di zaman modern saat ini dengan keterbukaan informasi yang bisa menghambat dalam proses implementasi tasawuf dalam pendidikan Islam.